101 freaky animals - Berger, Melvin. frey50; Berger, Gilda (New York, N.Y. : Scholastic, 2010)
Presents over one hundred interesting facts about animals from around the world, including armadillos, cuttlefish, giant clams, sharks, scorpions, and meerkats.
Includes index.
Keywords: Animals; Animals